Gender Differences in Life Satisfaction and Social Participation - Stephan Humpert (International Journal of Economic Sciences and Applied Research, 2013)
The paper deals with the effects of social participation activities on life satisfaction. Using the German General Social Survey (ALLBUS) for 2010, marginal effects of binary probit estimations on life satisfaction are presented. Strong gender differences are observable. While sport, welfare or parental activities affect only female life satisfaction, males are more affected by classical hobbies. As an interesting result that political activities, such as a political party or a union membership, have no or even negative effects. The general results may be interpreted in that way, that activities or memberships with influence in local fields with own responsibility and personal interest in a short of time, may be more satisfying than activities with more idealistic tasks and long run results, such as protecting nature or human rights.
Keywords: I31; D60; Z13; 330; Subjective Well-Being; Social Participation; German General Social Survey (ALLBUS)